Tindak Tutur Direktif dan Strategi Bertutur Guru dalam Pembelajaran Teks Biografi Siswa Kelas X SMAN 1 Kamang Magek - Latifa Zahra; Ena Noveria; Tressyalina Tressyalina; Herlin Triana (Universitas Muhammadiyah Magelang, 2026)
This study is motivated by the crucial role of language in the learning process, particularly the use of directive speech acts by teachers in teaching biographical texts. The limited variation in the use of directive speech acts, which tend to be direct and instructional, may affect students’ engagement and motivation during learning activities. Therefore, this study aims to (1) identify and describe the forms of directive speech acts used by the teacher, and (2) examine the speaking strategies applied in teaching biographical texts in a tenth-grade class at SMAN 1 Kamang Magek. This research employs a qualitative approach with a descriptive method. The data consist of the teacher’s utterances during the learning process, collected through recording and note-taking techniques. The findings reveal that there are five forms of directive speech acts used by the teacher, namely commanding, requesting, suggesting, demanding, and challenging, with commanding as the dominant form. In addition, several speaking strategies were identified, including bald on-record strategy, positive politeness, negative politeness, off-record strategy, and speaking in silence, with the bald on-record strategy being the most dominant. These findings indicate that the teacher’s speech practices are still predominantly oriented toward direct instruction. Therefore, it is necessary to develop more varied, communicative, and persuasive speaking strategies to enhance students’ active engagement and foster reflective thinking in learning biographical texts.